Peran Environmental, Social, Governance dalam Menilai Kinerja Keuangan (Studi Kasus pada Perusahaan Pertambangan Indonesia) - Mulyadi Mulyadi; Endah Nawangsasi; Endang Saryanti (ProBank, 2025)
This study aims to determine the role of Environmental, Social, and Governance in assessing the financial performance of mining companies. From a population of 55 mining companies with a purposive sampling method. The data analysis technique uses the first classical assumption, the second multiple linear regression then the t-test and the Adjusted R Squared test. The indicator used as the dependent variable is Financial Performance which is proxied by Net Profit Margin. This study uses secondary data and the type of research is quantitative. The results of the study obtained indicate that environmental has a positive but insignificant effect, social has a positive but insignificant effect, while governance has a negative and insignificant effect. The results of the Adjusted R Squared test show the contribution of the independent variable (ESG) to the dependent (Financial Performance) of 0.010 or 1%. This means that the role of Environmental, Social, and Governance in assessing financial performance is very small. This indicates that businesses that focus on environmental, social, and governance aspects do not directly impact the company's profitability in the short term. This can happen because it uses a net profit margin measure which requires a large initial investment, such as spending on environmentally friendly technology, employee welfare programs, or increasing transparency of governance. Such costs can depress short-term net income. Then the long-term benefits of ESG can be a reason that its effects can only be felt in the long term around 10-30 years. Thus, ESG efforts to improve operational cost efficiency in the short term will depress net income, so that NPM tends not to increase. However, in the long term ESG can increase efficiency, customer loyalty, reduce regulatory and litigation risks, which ultimately contribute to increasing the company's profitability.